Genetic variation of the native Rusa deer (Rusa timorensis) in Java and Bali (Indonesia) as revealed using non-invasive sampling - M. HAFIZHUL IMAN; PARAMITA CAHYANINGRUM KUSWANDI; SENA ADI SUBRATA (Society for Indonesian Biodiversity, 2024)
Abstract. Iman MH, Kuswandi PC, Subrata SA. 2024. Genetic variation of the native Rusa deer (Rusa timorensis) in Java and Bali (Indonesia) as revealed using non-invasive sampling. Biodiversitas 25: 355-360. Rusa deer is a vulnerable species with a large geographic range but natively inhabits Java and Bali. Despite the wide distribution, its native population is declining, raising a concern about a small population's adverse genetic effect. It encourages genetic studies to provide baseline data that has been vacant recently. This research aimed to demonstrate an application of non-invasive sampling to collect DNA samples and a simple procedure to obtain and analyze genetic data for the Rusa deer. This research also aimed to provide genetic variation of the native deer population as baseline data. The research sites were Baluran, Alas Purwo in East Java, and Bali Barat national parks from which fecal samples were collected. Moreover, 20 DNA samples were isolated from the feces using a kit (Dneasy PowerSoil Pro from Qiagen) and amplified at the control region gene using a forward: AAACCAGAAAAGGAGAGCAAC and a reverse: TCATCTAGGCATTTTCAGTGCC primer. The amplicons were sequenced, and the number of Haplotypes (Hn), Haplotype diversity (Hd), nucleotide diversity (p), site polymorphism, and phylogeographic tree were determined. The result showed that all the sequences had coverage of 100% and identity >98% with the Rusa timorensis sequence available in the GenBank. Furthermore, we found Hn = 11, Hd = 0.88, p = 0.005 and 30 site polymorphisms. Therefore, compared to an introduced population, the Rusa deer has a richer Hd and higher site polymorphism but a poorer p. Furthermore, we found that the Baluran population had high Hd, p, and is possibly forming a distinct clade.